2020
DOI: 10.1002/acp.3741
|View full text |Cite
|
Sign up to set email alerts
|

Conservatism positively predicted fading affect bias in the 2016USpresidential election at low, but not high, levels of negative affect

Abstract: Unpleasant affect fades faster than pleasant affect and this Fading Affect Bias (FAB) phenomenon is positively related to healthy outcomes and negatively related to unhealthy outcomes, which makes the FAB a healthy coping process/reaction. Rehearsal seems to be the cognitive mechanism responsible for the FAB. Although the FAB and its relation to healthy outcomes and rehearsal have been examined in many contexts, they have not been evaluated in the realm of politics. Therefore, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Gibbons et al (2017) showed a similar negative relation between the FAB and depression, but the FAB decreased slightly across the first three quintiles of depression, and it decreased much more across the last two quintiles of depression, disappearing far into the highest quintile of depression. Similarly, Gibbons, Thomas, and Dunlap (2018) showed that depression decreased from the second to the fifth quintile but then disappeared far into the highest quintile of depression.…”
Section: Introductionmentioning
confidence: 92%
“…Gibbons et al (2017) showed a similar negative relation between the FAB and depression, but the FAB decreased slightly across the first three quintiles of depression, and it decreased much more across the last two quintiles of depression, disappearing far into the highest quintile of depression. Similarly, Gibbons, Thomas, and Dunlap (2018) showed that depression decreased from the second to the fifth quintile but then disappeared far into the highest quintile of depression.…”
Section: Introductionmentioning
confidence: 92%
“…The data for the presidential election study came from four events (pleasant and unpleasant non-political events as well as the 2016 Presidential election [84] event and a comparably, but opposite, emotionally intense event) provided by 310 participants [85]. The data from the relationship study came from 12 events (3 pleasant and 3 unpleasant relationship events as well as 3 pleasant and 3 unpleasant non-relationship events) provided by 239 participants from the relationship study [86].…”
Section: Participantsmentioning
confidence: 99%
“…Although the political study was conducted within 3 months of the 2016 Presidential election, the other studies limited participants to events no older than 1 year. The time between initial event occurrence and test was only obtained in the election study [85].…”
Section: Materials Procedures Measures Design and Analysesmentioning
confidence: 99%
“…Similarly, although the FAB has emerged for memories of events associated with current relationships, it was not found for memories of past failed relationships (Zengel et al, 2019). A smaller FAB was also seen for memories of playing video games compared to non‐video game memories (Gibbons & Bouldin, 2019), and for memories of the 2016 presidential election compared to non‐political events (Gibbons et al, 2020). Thus, recent research into the FAB has shown that it is not necessarily universal across all types of events experienced, as it appears that characteristics of the event can moderate the extent to which usual healthy coping processes operate upon memories for those events.…”
Section: Introductionmentioning
confidence: 97%